Kwangju Biennale 2000- New Media Art : Scar - Gwangju Biennale Foundation (Gwangju Biennale Foundation, 2002)
Texts: Kang, Hong-goo; Kim, Joon; Bae, Young-hwan; Son, Jung-hyun; Lee, Hyeong-joo; Jun, Soo-hyun; Choi, Min-hwa; Hong, Ji-yeun; Zoltan Szegdy Maszak
English; Korean
Keywords: Korea; N4390-5098 Visual Arts- Exhibitions